Analysis and Planning of Punge Intersection Roundabout in Banda Aceh City - M. Isya; Yusria Darma; Rachmat Taufiqy; Inseun Yuri Salena (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2021)
The Punge intersection in Banda Aceh City is a four-armed intersection without traffic control devices such as traffic lights and roundabouts. The intersection performance from visual observation is currently very low, especially during peak hours. Therefore, it is presently considered necessary to evaluate road performance and carry out alternative handling planning. One alternative handling is to plan a roundabout at the intersection. Thus, this study aims to obtain road performance by comparing the use of a roundabout and without a roundabout. Analysis and planning using the MKJI and PTV Vissim 10.00-02 methods. It requires data on traffic volume, road geometry, and environmental conditions around the location. The analysis of roundabout planning with the widening of each arm with the MKJI and Vissim methods produces the level of services to deliver the best decisions for improving the intersection performance